2021
DOI: 10.1177/2324709621992207
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogression in a Patient With Hepatocellular Cancer Treated With Atezolizumab and Bevacizumab: A Case Report and Review of Literature

Abstract: Immune checkpoint inhibitors have emerged as a novel treatment in a wide variety of malignancies; however, it is associated with a distinctive array of side effects known as immune-related adverse events. Hyperprogression is defined as an accelerated growth of disease burden in patients treated with immunotherapy. Limited literature is available regarding hyperprogression in hepatocellular cancer. We report a case of a 36-year-old male with no past medical history who presented with nausea, vomiting, and abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The prevalence of PSPD and HPD across solid tumors is reported below 10% and 4–29%, respectively 26,27 . Limited literature is available regarding PSPD and HPD in HCC 28,29 . In our series, seven patients (5.8%) experienced an initial progressive disease defined by the visualization of new lesions and/or increased target lesions, but exacerbation of clinical signs or symptoms was not observed, thus these patients received a confirmation radiological assessment 8 weeks later, six of them was confirmed PD with the second CT scan, while one of them determined to have PD until the third CT scan.…”
Section: Discussionmentioning
confidence: 74%
“…The prevalence of PSPD and HPD across solid tumors is reported below 10% and 4–29%, respectively 26,27 . Limited literature is available regarding PSPD and HPD in HCC 28,29 . In our series, seven patients (5.8%) experienced an initial progressive disease defined by the visualization of new lesions and/or increased target lesions, but exacerbation of clinical signs or symptoms was not observed, thus these patients received a confirmation radiological assessment 8 weeks later, six of them was confirmed PD with the second CT scan, while one of them determined to have PD until the third CT scan.…”
Section: Discussionmentioning
confidence: 74%
“…Hyperprogression is an extraordinary response to immunotherapy including CAR-T treatment, which is characterized by accelerated disease progression and worsening survival outcomes. 3 6 7 8 It is reported that the incidence of hyperprogression ranges from 4 to 29%, 6 which may occur in various tumors, such as lymphoma, 9 non-small-cell lung cancer, 10 hepatocellular carcinoma, 11 12 renal cell carcinoma, 13 melanoma, 14 breast cancer, 15 sinonasal cancer, 16 17 bladder carcinoma, 18 and gastrointestinal cancer. 19 However, limited literature is available regarding hyperprogression in RMS.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 137 found that HCC patients with baseline NLRs greater than 6 had a 46.2% risk of progression according to univariate analysis. Similarly, Singh et al 138 identified an NLR cutoff value greater than 4.125 as accurate in predicting HPD based on subject characteristic curves. They also found that high NLR scores predicted poorer survival outcomes after PD-1 administration.…”
Section: Hyperprogressionmentioning
confidence: 98%
“…Several retrospective studies and case reports have evaluated TGK, TGR, TTF, and other metrics in the diagnosis of HPD in patients with HCC. [136][137][138][139][140][141][142][143] Among them, Kim et al 137 suggested that the TGK ratio (TGK R ) and TGR should increase at least four fold compared with pretreatment, or the absolute change in TGR (DTGR) should increase by more than 40%. These criteria aim to minimize the misdiagnosis of pseudo-HPD and are more applicable to HCC patients, although they still require validation in prospective studies.…”
Section: Hyperprogression Definition and Evaluation Criteria Of Hpdmentioning
confidence: 99%
See 1 more Smart Citation